Pengaruh Pola Asuh Dan Paparan Media Informasi Terhadap Pernikahan Dini Pada Remaja : Studi Literatur - Lyberty, Ervyana; Rahmawati , Alfiah (Jurnal MID-Z (MIDWIFERI ZIGOT), 2025)
One of the problems that arises in society is early marriage among teenagers. There are many factors that cause early marriage, including knowledge, socio-cultural factors, education, economic status, the role of peers, parenting patterns, and exposure to information media. This literature study aims to determine the relationship between parenting patterns and exposure to information media on early marriage in adolescents. The research design used to compile this article is a literature review method based on the latest previous research articles published from 2019 to 2024. The online database sources used include PubMed and Google Scholar, the articles searched are in accordance with The keywords applied are parenting patterns, exposure to information media and early marriage. The number of articles reviewed in this literature review was 15 articles. Among the various factors both internal and external to early marriage, parenting is a factor that has quite an influence on this incident, because the approach used by parents will affect the way of thinking, behaving, and decision-making. In addition, the lack of exposure to information media also has an impact on the occurrence of early marriage among teenagers. There is a relationship between the parenting style applied and exposure to information media and the incidence of early marriage in adolescents.